The crisis of international order and the power of the United States - Ashcallay Samaniego, Samuel (2024)
We are currently witnessing a crisis in the international liberal order, a system that has governed relationships among global actors for nearly eight decades. This order has been built upon key principles such as economic openness, multilateralism, security cooperation, and democratic solidarity. Originating as a framework largely confined to the Western world during the Cold War era, it has since become the dominant global paradigm following the events of 1991. The establishment of the United States as a major power played a pivotal role in shaping this order, along with its leadership in constructing governance institutions in collaboration with other liberal democracies. This article aims to analyze the evolution of the international liberal order, focusing on the various stages of its development. By examining the foreign policy and exercise of power by the United States, we seek to gain insights into the current crisis facing this order and explore potential pathways for its future.